Community Acceptance Assessment of the Covid-19 Vaccination Program in the South Kalimantan Region - Iwan Aflanie; Mohammad Bakhriansyah; Istiana; Fauzie Rahman; Vina Yulia Anhar; Diauddin; Yusef Dwi Jayadi; Husnul Fatimah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Conducting an effective Covid-19 vaccine is a global public health necessity in containing the pandemic. Vaccines are one of the most reliable and cost-effective public health interventions ever implemented that are saving millions of lives each year. The purpose of this study was to identify public acceptance of the Covid-19 vaccination program in the South Kalimantan region. Quantitative research by using a cross-sectional approach. The number of samples is 252 people. The sampling technique is accidental sampling. The study was conducted in South Kalimantan Province, Indonesia. Predictors of acceptance of the vaccine program were identified from vaccination status, views on vaccine effectiveness, vaccine safety, pandemic conspiracy, trustworthiness of information about Covid-19, and willingness to pay for vaccines. Data collection was done online using a Google Form questionnaire. Based on the predictors of acceptance of the covid-19 vaccination program, it can be seen that the majority support the vaccination program in helping prevent the transmission of Covid-19.